IMPROVING STUDENT’S VOCABULARY BY USING JUMBLED LETTERS AND INDEX CARD MATCH AT THE FIFTH YEAR OF SD MUHAMMADIYAH 2 KAUMAN SURAKARTA IN 2010/2011 ACADEMIC YEAR - MIHARTI, HARYANI AGUSTINA (2011)
This study is aimed improving students’ vocabulary by using Jumbled Letters and Index Card Match. The objectives of the study are to describe the improvement of students’ vocabulary by using Jumbled Letters and Index Card Match and to know the strength and weakness of improving students’ vocabulary by using Jumbled Letters and Index Card Match at the fifth year of SD Muhammadiyah 2 Kauman Surakarta. In achieving the objectives of this research, the writer uses Classroom Action Research (CAR). Each cycle of this action research consists of four steps: planning, acting, observing and reflecting. The research was held in SD Muhammadiyah 2 Kauman Surakarta especially V A class consisting of 40 students. In analyzing the data taken from observation, test and interview, the writer uses both qualitative and quantitative analysis. There are two cycles in this action research in which each cycle is conducted in two meetings. The result showed the mean score of pre-test is 50.5, in post-test I is 70.5 and in post-test II is 80.8. The result of this research shows that the students’ writing vocabulary improves. The strength of improving vocabulary by using Jumbled Letters and Index Card Match is the students became more active, creative, and reduce their error possibility in writing vocabulary. The weakness is the students were made some noise when joining Index Card Match activity because of the research conducted in the large class, so the teacher should have an extra energy to handle the class. Thus, it can be said that teaching vocabulary by using Jumbled Letters and Index Card Match is successful to improve the students’ vocabulary in SD Muhammadiyah 2 Kauman Surakarta.